2011
DOI: 10.1111/j.1472-4642.2011.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of Australian acacias: important mediator of invasiveness?

Abstract: Aim Reproductive traits are important mediators of establishment and spread of introduced species, both directly and through interactions with other life-history traits and extrinsic factors. We identify features of the reproductive biology of Australian acacias associated with invasiveness.Location Global.Methods We reviewed the pollination biology, seed biology and alternative modes of reproduction of Australian acacias using primary literature, online searches and unpublished data. We used comparative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(178 citation statements)
references
References 138 publications
(302 reference statements)
4
172
1
1
Order By: Relevance
“…In A. longifolia, Kenrick and Knox (1982) found up to 12 seeds per pod as a result of open pollination in Australia, while we found 10 seeds and Correia et al (2016) found less than 6 seeds in Portugal. Acacia is a genus that invests a lot of resources in massive flowering (Gibson et al, 2011). Acacia longifolia flowering branches are very abundant on a given plant, and number of inflorescences and flower heads and flowers are impressive (Tybirk, 1997;Fernandes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In A. longifolia, Kenrick and Knox (1982) found up to 12 seeds per pod as a result of open pollination in Australia, while we found 10 seeds and Correia et al (2016) found less than 6 seeds in Portugal. Acacia is a genus that invests a lot of resources in massive flowering (Gibson et al, 2011). Acacia longifolia flowering branches are very abundant on a given plant, and number of inflorescences and flower heads and flowers are impressive (Tybirk, 1997;Fernandes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, two insects have recently provided a significant reduction in Acacia cyclops seed production (Impson & al., 2004;Post & al., 2010), and biological control appears to be the most effective and cost-saving method for curbing the Acacias reproductive potential and related invasiveness (Richardson & Kluge, 2008). Because of the substantial absence of vegetative propagation (Gill, 1985;Gibson & al., 2011), A. cyclops establishment and invasive success is strongly dependant on a copious production of viable seeds and their subsequent dispersal (Milton & Hall, 1981;Holmes, 1988). In particular, its seeds with attractive arils are well adapted for bird dispersal whilst they are retained in the canopy (Glyphis & al., 1981), but once the seeds have fallen to the ground, ants and small rodents may also spread them or carry them into the deeper soil layers, thus increasing the likelihood of their being added to the soil seed-bank (Holmes, 1989;Richardson & Kluge, 2008 fery & al., 1988;Holmes, 1989), rather it depends upon chemical scarification, notably after the passage through the gut of birds, or to only moderate heating in order to break dormancy (Glyphis & al., 1981;Gill, 1985;Jeffery & al., 1988).…”
Section: Global Distribution and Ecology Of Acacia Cyclopsmentioning
confidence: 99%
“…Meanwhile, interference by construction activities enhances invasion ability of A. mearnsii, because it can help break seed dormancy underground. Finally, the weedy characteristics are also key drivers of invasive success (Gibson et al 2011;Low 2012), such as long-lasting inflorescences, a variety of dispersal pathways, the ability to re-sprout and germinate in abundance following disturbance, and high growth rates. All result in the emergence of a large number of tree seedlings after environmental adaptation in grass-planting area at the airport.…”
Section: Possible Factors Affecting Invasion Successmentioning
confidence: 99%
“…The trees attract many birds to rest on them, which increases the opportunities for bird strike at the airport (Gallagher et al 2011;Gibson et al 2011;Li 2014;Li et al 2011;Xu et al 2011). We undertook an A. mearnsii invasion survey, which is the first time in China that a detailed monitoring investigation of this species has been performed.…”
Section: Introductionmentioning
confidence: 99%